Association between subtypes of metabolic syndrome and prognosis in patients with stage I endometrioid adenocarcinoma: A retrospective cohort study - Chen, Man-qi; Lin, Hai-xue; Liang, Jin-xiao; Wu, Miao-fang; Li, Jing; Wang, Li-juan (Frontiers in Oncology, 2022)
Purpose: To investigate the association between subtypes of metabolic syndrome (MetS) and prognosis of patients with stage I endometrioid adenocarcinoma. Patients and Methods: Patients with stage I endometrioid adenocarcinoma who received surgical treatment as primary therapy at the Department of Gynecology of the Sun Yat-sen Memorial Hospital between June 2015 and December 2019 were retrospectively enrolled. According to the diagnosis criteria of MetS, the patients were categorized as patients without MetS, patients with MetS but without raised fasting plasma glucose (FPG, including previously diagnosed diabetes), and patients with MetS and raised FPG. All the included patients were followed from the dates of surgery until death, June 2021, or loss to follow-up, whichever came first, and cancer recurrence (including metastasis) was studied as the main outcome. Cox regression was used to evaluate the associations between subtypes of MetS and the study outcome adjusting for potential confounding factors. Results: Among the included 387 patients with stage I endometrioid adenocarcinoma, 193 (49.9%) were without MetS, 65 (16.8%) were with FPG not involved MetS, and 129 (33.3%) were with raised FPG involved MetS. With a median follow-up of 1253 days, the cumulative incidence of cancer recurrence was 8.76% (95% confidence interval (CI) 2.5-14.62%), 28.31% (95%CI 2.33-47.38%), and 7.54% (95%CI 1.54-13.17%), respectively. After adjusted for age, menopause, histological grade, tumor size, lymph-vascular space invasion, deep myometrial invasion, and treatments, comorbid FPG not involved MetS is a stronger risk factor of cancer recurrence than comorbid raised FPG involved MetS (hazard ratio 2.82 (95%CI 1.10-7.24) versus 1.18 (95%CI 0.45-3.13)) when compared to patients without MetS. Conclusion: Comorbid MetS generally presents as a risk factor of poor prognosis in patients with stage I endometrioid adenocarcinoma after surgical treatment, but the magnitude of the association may vary between subtypes, in which FPG not involved MetS appears to be predominant.